2023
DOI: 10.1021/acs.cgd.2c01210
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Tailoring and Functional Group Fusion Strategy for Developing Photochromic Compounds: A Case Study for Pyridinedicarboxylic Acid

Abstract: Hybrid photochromic materials (HPMs) can produce novel photoresponsive properties, thanks to the synergistic effect of each component. One of the widely explored ways toward a novel HPM system is the utilization of the phototriggered electron transfer (ET) mechanism. In this work, the photochromic functionality of pyridinedicarboxylic acid with the chemical formula of H 5), has been first proved via the ligand tailoring and functional group fusion strategy. The photogenerated radicals derived from ET were expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Pyridinecarboxylate ligands contain both electron-accepting pyridyl and electron-donating carboxyl moieties, which is beneficial for the obtainment of PMOCs. Our recent work has demonstrated the feasibilities of 2,6-pyridinedicarboxylic and 2,4-pyridinedicarboxylic acids for developing PMOCs . Actually, the conjugated degree of pyridyl moieties, the number of carboxyl moieties, and the distance between N pyridyl and O carboxyl may have potential influence on the final photochromic performance of the resultant MOCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyridinecarboxylate ligands contain both electron-accepting pyridyl and electron-donating carboxyl moieties, which is beneficial for the obtainment of PMOCs. Our recent work has demonstrated the feasibilities of 2,6-pyridinedicarboxylic and 2,4-pyridinedicarboxylic acids for developing PMOCs . Actually, the conjugated degree of pyridyl moieties, the number of carboxyl moieties, and the distance between N pyridyl and O carboxyl may have potential influence on the final photochromic performance of the resultant MOCs.…”
Section: Resultsmentioning
confidence: 99%
“…To generate isomeric PMOCs, we introduced 2,2′-bipyridine-4,4′-dicarboxylic acid (H 2 bpdc) into suitable metal salts to yield desirable isomeric PMOCs according to the following thoughts: (a) H 2 bpdc contains both ED- and EA-moieties, which is helpful for overcoming the coordination competition of PMOCs based on mixed ligands. , (b) The fully deprotonated bpdc 2– , as a polydentate N/O-ligand, exhibits assorted coordination modes and will compensate the charge of Pb 2+ , which is advantageous to the yield of isomeric products . (c) Rigid dipyridine units with good conjugation are beneficial to stabilize the photogenerated radicals .…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the EPR data, single crystal structure analysis, and controlled experiment, it is revealed that photochromic behaviors are triggered by a photoinduced electron transfer process in which O atoms of the ketone group accept electrons to generate radical anions, and DMF molecules as electron donors can contribute to the photoinduced electron transfer process. 34,41–43…”
Section: Resultsmentioning
confidence: 99%
“…This characteristic suggests that BCA itself may exhibit PET properties and form a charge-separated state. 35,36 Secondly, BCA features two carboxyl groups and two nitrogen atoms, enabling coordination with metal ions in various modes, thus offering the potential to yield a series of photochromic complexes. 37 Thirdly, BCA typically adopts a planar structure in reported BCA-based complexes, facilitating strong conjugation and intermolecular weak interactions within the complexes, thereby beneficial for NIR-II absorption of charge-separated states.…”
Section: Introductionmentioning
confidence: 99%